2017
DOI: 10.1021/acs.biochem.7b00483
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Effects of O-Linked Glycans on Protein Folding

Abstract: Protein O-glycosylation is a diverse, common, and important post-translational modification of both proteins inside the cell and those that are secreted or membrane-bound. Much work has shown that O-glycosylation can alter the structure, function, and physical properties of the proteins to which it is attached. One gap remaining in our understanding of O-glycoproteins is how O-glycans might affect the folding of proteins. Here, we took advantage of synthetic, homogeneous O-glycopeptides to show that certain gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 75 publications
4
9
0
Order By: Relevance
“…For both the CBM and the linker mutant libraries, however, we stress that the proteolytic stability assays conducted here do not include a fully comprehensive suite of plant or microbial proteases that T. reesei cellulases likely encounter in nature, such that stability imparted by both CBM and/ or the full suite of linker O-glycans (including the smaller Ser cluster) may be important in other environmental conditions not assayed for in this study. Notably, other functional roles have also been proposed for these glycans: recently, direct evidence has shown that CBM O-glycosylation significantly aids the folding of TrCel7A family 1 CBM (40). Additionally, we stress that the TrCel7A family 1 CBM remains a useful model system in which to probe the biophysical effects of O-linked glycosylation on a small, folded domain that is readily accessible via chemical synthesis techniques.…”
Section: Discussionmentioning
confidence: 69%
“…For both the CBM and the linker mutant libraries, however, we stress that the proteolytic stability assays conducted here do not include a fully comprehensive suite of plant or microbial proteases that T. reesei cellulases likely encounter in nature, such that stability imparted by both CBM and/ or the full suite of linker O-glycans (including the smaller Ser cluster) may be important in other environmental conditions not assayed for in this study. Notably, other functional roles have also been proposed for these glycans: recently, direct evidence has shown that CBM O-glycosylation significantly aids the folding of TrCel7A family 1 CBM (40). Additionally, we stress that the TrCel7A family 1 CBM remains a useful model system in which to probe the biophysical effects of O-linked glycosylation on a small, folded domain that is readily accessible via chemical synthesis techniques.…”
Section: Discussionmentioning
confidence: 69%
“…By taking advantage of the relatively slow kinetics in disulfide bond formation, the Tan group was able to confirm the importance of glycosylation in regulating the folding of a family 1 carbohydrate-binding module (CBM). Additionally, they were able to elucidate the glycosylation site-, glycan size- and structure-specific effects of O-glycosylation on the folding using a mass spectrometry-based approach (P. K. Chaffey, X. Guan, X. Wang, et al, 2017).…”
Section: Biological Impact Of Protein Glycosylationmentioning
confidence: 99%
“…85,86 More importantly, the ready availability of the WW domain via chemical synthesis allowed the exploration of the origin of the stabilizing effect involving the enhanced aromatic sequons. 77 Using chemical synthesis, Kelly and co-workers were able to site specifically incorporate uniformly 13 C-and 15 N-labeled amino acids to loop 1 of the Pin WW domain. 87 The isotopically labeled residues made it possible to gather highresolution nuclear magnetic resonance (NMR) structures of engineered variants carrying fiveor six-residue enhanced aromatic sequons glycosylated with a single GlcNAc at Asn19 (Figure 7).…”
Section: ■ Case Studies: Protein N-glycosylationmentioning
confidence: 99%
“…13 More recent work has shown that protein glycosylation can also have intrinsic effects on a protein's folding independent of the quality control checking chaperones. 14,15 Glycans have been shown to act as specific ligands that mediate the attachment of certain cells to their target tissues or that initiate signal transduction pathways within target cells. 16 Because they are often very hydrophilic and can be quite bulky, the attachment of glycans can significantly alter the surface properties of proteins and thus affect protein−protein interactions.…”
mentioning
confidence: 99%